O Álbum Ilustrado da Comarca de Rio Preto e a Educação Enunciada (1920-1929): histórias, memórias e identidades alentadas em verbo-visualidade - Silva, Vinicius Vieira (2019)
The spatial transformations that took place in the countryside of São Paulo State of the years 1920 served as a motto for intellectuals who strove to be the heralds of modernization. Given this scenario, it was proposed screening of the social function of the enunciation of the propagandistic Illustrated Album of the County of Rio Preto, whose processes of idealization, organization and editing emanated of journalistic enthusiasm of Abílio Augusto Abrunhosa Cavalheiro. To this end, analyzed, in the light of theoretical and methodological propositions of Cultural History and Post-structuralist Discourse Analysis, the social circuit of production, circulation and reception of such printed, as well as your photographic materiality. Thus, it was identified that the themes related to education, especially under its school manifestation, were recurrent in the ideological formation of its discursive subject and in the concrete dimension of the typographic object in question, being at the intersection of the utterances that emphasized the unrestrained love of the fatherland. With this, it was concluded that the verb-visual enunciation of artifact investigated if he based on an imanent expectation of the popular and official instruction, because, by propagating the existence of this, instilled a certain familiarity with the so-called new order of society, it was stressed the stability that financial investments dispensed in the region would have, and expanded the persona of its artificer as one of the individuals who have contributed rigorously to the civilization of the territories encompassed in it.